EFFECTS OF SWIMMING TECHIQUES ON FINAL RESULT IN 200M INDIVIDUAL MEDLEY - Goran Dimitrić; Maja Batez; Milica Bogdanovski; Miroslav Petrović; Igor Glavičić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Swimming results are permanently improving. Results in individual medley disciplines are also improving. Individual medley disciplines are consist of all four swimming techiques. Results in these disciplines depende amongother things, on the swimming quality in all techniques. In 200m individual medley, each techinque implies 50m swimming, in following order: butterfly, backstroke, breast stroke and free style. The aim of this paper is to determine individual affect of each swimming technique on 200m individual medley final result. Reasearh was based on the achieved times of 30 male and 30 female swimmers who participated in 200m individual medley qualifications on European chanpionship - Szczecin 2011, Poland. According to adequate statistical methods and analysis of results, certain conclusions will be derived